Vegetative Propagii.tion of Cinchona ledgeriana Moens. by Modified Mound and Trench Layerage Methods - Foning Ramsong, A. (Indian Forester, 1967)
The bark of Cinchona ledgeriana Moens. Forms the basic raw material for the manufactureof quinine-an anti-malarial drug, The introduction of this commercially important plant in India dates back to 1860 when Sir Clements Markham brought some Cinchona seeds and plants to India from South America. At present West Bengal and Madras are the two States of Indian Union where we have some thousands of acres of Cinchona Plantations run by the Department concerned of the respective Government. In recent past, the impact of various factors had rendered the future of the Cinchona Industry somewhat uncertain. However, it has again regained its place of pride in world market and is now a very much sought after commodity, and a foreign exchange earner for the country.Breeding of this plant along proper scientific lines for stabilising the industry's future was considered desirable and accordingly, work in this direction has been taken up by the Directorate of Cinchona, West Bengal. In this paper are described new techniques (vegetative methods) of propagation that are being developed by the Horticultural wing of the Research Section, Cinchona Directorate, West Bengal, stationed at Mungpoo in the district of Darjeeling